The Role of Community College Attendance in Shaping Baccalaureate Recipients' Access to Graduate and Professional Education. (March 2019) - Wang, Xueli; Lee, Yen; Wickersham, Kelly
Using data from the Baccalaureate and Beyond Longitudinal Study and propensity score matching techniques, this study examined the impact of having attended a community college on baccalaureate recipients' access to graduate and professional schools in general and how previous community college attendance influenced student enrollment in different professional and graduate programs. Our findings revealed that there was no significant negative or positive effect of community college attendance on access to graduate or professional school or on program enrollment choices. These results imply that community college attendance does not limit access to graduate and professional education and holds the promise to complement the route to graduate and professional school.